2013
DOI: 10.1074/jbc.m112.396309
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a His-Asp-Cys Catalytic Triad Essential for Function of the Rho Inactivation Domain (RID) of Vibrio cholerae MARTX Toxin

Abstract: Background:The Vibrio cholerae MARTX toxin Rho inactivation domain (RID Vc ) currently has an unknown mechanism of action. Results: Residues His-2782, Leu-2851, Asp-2854, and Cys-3022 are shown to be essential for RID Vc activity. Conclusion: His-Asp-Cys form a catalytic triad necessary for enzymatic modification of the cellular target. Significance: RID effectors are Clan CE cysteine endopeptidases essential for Rho GTPase inactivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 37 publications
0
45
0
Order By: Relevance
“…Alanine scanning mutagenesis has proven to be a useful tool to identify critical residues for other of MARTX effector domains 12,31,38 . Alignment of DUF5 amino acid sequences from 5 MARTX toxins, Plu2400, and PMT showed that there are only 16 residues (8.5%) that are 100% identical across all proteins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alanine scanning mutagenesis has proven to be a useful tool to identify critical residues for other of MARTX effector domains 12,31,38 . Alignment of DUF5 amino acid sequences from 5 MARTX toxins, Plu2400, and PMT showed that there are only 16 residues (8.5%) that are 100% identical across all proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The actin crosslinking domain (ACD) covalently links actin monomers via an isopeptide bond leading to actin cytoskeletal destruction 710 . The Rho GTPase inactivation domain (RID) disables the Rho regulatory pathway resulting in loss of active Rho and thereby to cytoskeleton depolymerization 11,12 . The ExoY domain is an adenylate cyclase 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effector is a member of the circular permuted thiol peptidase family, although the RID is predicted to have a distinct arrangement of its catalytic site compared to other proteins in this family (43, 44). After delivery to the cytosol by processing from CPD, the presence of a four helical bundle type membrane localization domain targets the RID to the plasma membrane (45, 46).…”
Section: Martx Toxins Of V Choleraementioning
confidence: 99%
“…As Rho is a master regulator of stress fiber assembly, cells treated with RID round due to lack of cytoskeletal assembly (47). Interestingly, although both ACD and RID independently affect polymerized actin, the domains are not synergistic, and thus, neither actin crosslinking nor Rho inactivation is accelerated by the presence of the other domain in the same toxin (26, 44). …”
Section: Martx Toxins Of V Choleraementioning
confidence: 99%